Patient-reported financial distress in cancer: a systematic review of risk factors in universal healthcare systems - Pauge, Sophie; Surmann, Bastian; Mehlis, Katja; Züger, Andrea; Richter, Luise; Menold, Natalja; Greiner, Wolfgang; Winkler, Eva C. (Cancers, 2021)
Financial toxicity is a side effect of cancer that results from the perceived financial distress an individual may experience in the course of the disease. The purpose of this paper is to analyse underlying factors related to subjective financial distress in high-income countries with universal healthcare coverage. A systematic literature review was conducted to identify qualitative and quantitative studies of cancer patient-reported subjective financial distress by performing a search in the databases of PubMed, PsycINFO and CINAHL up to December 2020. A qualitative synthesis was performed linking the time-dependent occurrence of risk factors to derived categories of risk factors. Out of 4321 identified records, 30 quantitative and 16 qualitative studies were eligible. Classification of risk factors resulted in eight categories with a total of 34 subcategories. Subjective financial distress is primarily determined by pre-diagnosis sociodemographic- factors as well as financial and work factors that might change during the course of the disease. The design of healthcare and social security systems shapes the country-specific degree of subjective financial distress. Further research should focus on evolving multidisciplinary intervention schemes and multidimensional instruments for subjective financial distress to account for identified risk factors in universal healthcare systems more precisely.
This article belongs to the Special Issue Systematic Reviews of Patient-Reported Outcomes in Patients with Cancer
Gesehen am 10.02.2022